Analysis of urinary microRNAs in chronic kidney disease. (20th July 2012) - Beltrami, Cristina; Clayton, Aled; Phillips, Aled O.; Fraser, Donald J.; Bowen, Timothy
Abstract : Kidney biopsy is the gold-standard diagnostic test for intrinsic renal disease, but requires hospital admission and carries a 3% risk of major complications. Current non-invasive prognostic indicators such as urine protein quantification have limited predictive value. Better diagnostic and prognostic tests for chronic kidney disease patients are a major focus for industry and academia, with efforts to date directed largely at urinary proteomic approaches. microRNAs constitute a recently identified class of endogenous short non-coding single-stranded RNA oligonucleotides that regulate gene expression post-transcriptionally. Quantification of urinary microRNAs offers an alternative approach to the identification of chronic kidney disease biomarkers.